Desain Model Jaringan IP Combat Management System pada Kapal Perang Republik Indonesia Menggunakan GNS3 - Prathama Adibrata, Randika; Sahiri, Erpan (Computer Science and Information Technology, 2026)
The modernization of the Primary Weapon Systems (Alutsista) on the Republic of Indonesia Warships (KRI) demands an integrated Combat Management System (CMS). The main problem faced is the shift of military communication systems toward Internet Protocol (IP)-based systems and Indonesia's dependence on foreign-made CMS technology. To overcome these problems, this research aims to design a new IP network architecture specifically tailored for KRI CMS operations and to test its functionality. The proposed solution is the design of a hybrid physical topology, combining the advantages of a star topology at the internal level of the Central Server Cabinet (CSC) and a partial mesh topology between cabinets. Additionally, data communication management is logically optimized using Virtual Local Area Networks (VLAN). The problem-solving method is conducted through modeling in the Graphical Network Simulator 3 (GNS3), followed by functional validation testing. The network simulation proves the seamlessness of comprehensive data exchange, indicated by successful inter-device connectivity across all test scenarios. The implementation of VLAN segmentation is proven successful in isolating data paths, ensuring that real-time tactical command flows can be distributed without being disrupted by high-capacity video loads. Overall, this network architecture design is proven to be robust and efficient in meeting operational standards that require redundancy, eliminating the risk of a single point of failure, and providing scalability for future upgrades. This architectural design is expected to serve as a solid blueprint for the domestic industry to support self-reliance in national defense technology.